Influence of type of compatibilizer on the rheological and mechanical behavior of LCP/TP blends under different stationary and nonstationary shear conditions - Filipe, Susana (2005)
The addition of small amounts of liquid-crystalline polymers to thermoplastics leads to the formation of in situ–reinforced materials, with improved processability and mechanical properties. Nevertheless, the lack of adhesion between the thermoplastic and the liquid-crystalline polymer often occurs, thus requiring the use of compatibilizers. In this case, the results of several previous works show that there is an improvement of strength, usually accompanied by a decrease of toughness and, thus, the interest of LCP/TP blends for industrial applications will certainly increase if both strength and toughness are obtained. Additionally, the emphasis of previous studies has been on the evaluation of the properties of the blend under stationary conditions and not under non-stationary ones, which are, in fact, those most relevant to processing sequences. Thus, the present work focuses on the influence of type of compatibilizer on the mechanical and rheological properties of polypropylene/LCP blends under nonstationary conditions. In terms of mechanical properties, the traditional increase of tensile strength was obtained for all compatibilizers, which was essentially due to the formation, during processing, of thinner and longer fibrils of LCP dispersed in the matrix than those observed for the noncompatibilized blends. Additionally, an improvement of the impact strength and flexural modulus was also observed for the blend in which a compatibilizer with an elastomeric nature was used. Rheologically, the experiments most sensitive to the structure were those performed in transient shear, with an increase of the transient stress (in the form of an overshoot) of different magnitudes being observed for the different compatibilizers.